2022
DOI: 10.1002/ijgo.14478
|View full text |Cite
|
Sign up to set email alerts
|

The significance of TNF‐α and MMP‐8 concentrations in non‐invasively obtained amniotic fluid predicting fetal inflammatory response syndrome

Abstract: Objective: To determine the significance of tumor necrosis factorα (TNFα) and matrix metalloproteinase-8 (MMP-8) in vaginally obtained amniotic fluid predicting fetal inflammatory response syndrome (FIRS) after preterm premature rupture of membranes (PPROM). Methods:In this prospective case-control study, TNFα and MMP-8 concentrations were evaluated in vaginally obtained amniotic fluid from women with PPROM at 22-34 weeks of pregnancy. Biomarkers' concentrations were determined using an enzyme-linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, we sought to compare the association of suPAR with other amniotic in ammatory biomarkers, such as IL-6, TNF-α, and matrix metalloproteinase-8 (MMP-8). The signi cance of these biomarkers in noninvasively obtained amniotic uid predicting FIRS was reported previously [20,21].…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, we sought to compare the association of suPAR with other amniotic in ammatory biomarkers, such as IL-6, TNF-α, and matrix metalloproteinase-8 (MMP-8). The signi cance of these biomarkers in noninvasively obtained amniotic uid predicting FIRS was reported previously [20,21].…”
supporting
confidence: 66%
“…Patients with inadequate amniotic uid samples, such as insu cient volume or containing mucous and/or blood, were also excluded. Additional amniotic uid biomarkers, whose prognostic value has already been reported in previous publications [20,21], were evaluated during the study. For the assessment of suPAR, due to the association of suPAR with hypertensive diseases, we retrospectively excluded all cases with maternal hypertensive disorders for the suPAR analysis [19].…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, we sought to compare the association of suPAR with other amniotic inflammatory biomarkers, such as IL-6, TNF-α, and matrix metalloproteinase-8 (MMP-8). The significance of these biomarkers in noninvasively obtained amniotic fluid predicting FIRS was reported previously [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 59%
“…Women with confirmed intra-amniotic infection or intrauterine inflammation diagnosed by raised interleukin levels and matrix degrading enzymes at amniocentesis at 18.9 weeks (median) gestation are at risk of preterm delivery [44] . Elevated cord levels of inflammatory cytokines interleukins IL-1β, IL-6, IL-8 and TNF-α have been reported in prematurely born infants [45] , [46] . Animal models have also indicated that infection and inflammation may alter lung development in utero.…”
Section: Discussionmentioning
confidence: 99%